Analisis Potensi dan Kontribusi Retribusi Pelayanan Persampahan/Kebersihan Terhadap Retribusi Daerah di Kota Banjarmasin - Paramadina, Natasya; Sa'roni, Chairul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine how big determine the contribution of the Waste/Cleaning Service Retribution to the Regional Retribution, the growth rate of the waste /cleaning service retribution and to determine the potensial categories generated by the waste/cleaning service retribution in Banjarmasin City in 2010-2019. This research was conducted in Banjarmasin City using primary and Secondary data. Primary data is data about efforts and obstacles in collecting waste/cleaning service retribution in Banjarmasin City. While the secondary data is the target data and the realization of the waste/cleaning service retribution and the regional retribution for Banjarmasin City. The method in research is descriptive quantitative. The result of this study indicate that the average contribution of waste/cleaning service retribution is 36,02% greater than the average contribution of 3,02% for regional retribution which means contribution of the waste/cleaning service retribution to the regional retribution is potensial. The growth rate of average waste/cleaning service retribution is 10,64%, which means that the growth rateis positive. The potensial retribution for waste/cleaning service retribution in 2010-2019 is included in the prime category because of its potensial contribution and positive growth rate.